Quarter Century Management of Chronic Ureteropelvic Junction Obstruction in a Solitary Kidney with a Ureteral Stent - Abedi, Garen (J Endourol Case Rep, 2018)
Background: The ureteral stent provides a conduit for urinary drainage from the kidney to the bladder and is integral to contemporary urologic practice. A ureteral stent is often utilized in acute conditions to prevent or overcome obstruction; however, in nonsurgical patients, because of disease or preference, a ureteral stent may be used as a last resort for long-term management of a stricture in lieu of a nephrostomy tube. This case highlights a patient whose chronic ureteral obstruction has been managed with an indwelling ureteral stent for 25 years; remarkably, stent exchanges are currently required only every 2 years. Case Presentation: A 33-year-old man initially presented with a solitary left kidney and a ureteropelvic junction obstruction. The patient's right kidney was nonfunctioning since childhood because of a presumed ureteropelvic junction obstruction with grade IV hydronephrosis. The patient underwent two failed open repairs of the left kidney in the 1980s, resulting in a totally intrarenal, constricted renal pelvis; an endopyelotomy in 1992 also failed and required angioembolizaton of a segmental renal vessel. The patient refused any further surgical procedures and thus has been managed exclusively with a 7/14F × 28 cm endopyelotomy stent (Boston Scientific(®)) for 25 years; the interval between stent changes was slowly expanded until they are now being done at 2-year intervals. The patient has not developed recurrent urinary tract infections, stent colic, or stent encrustation. Conclusion: Patients who require chronic indwelling ureteral stents are rare. In this situation, with careful monitoring, the interval between stent exchanges was extended to 2 years, thereby precluding a chronic nephrostomy tube.